ATV mortality in the United States, 2011-2013 - Lagerstrom, Elise, author; Gilkey, David, advisor; Rosecrance, John, advisor; Magzamen, Sheryl, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2015)
The purpose of this study is to examine contributing factors of ATV injuries and deaths through application of the Agent-Host-Environment epidemiological model. By analyzing the associations between contributing factors and classifying these factors based on the model, appropriate intervention strategies may be identified. All US incident reports of ATV fatalities and injuries between 2011 and 2013 were obtained from the Consumer Product Safety Commission (CPSC). Each report was read and coded based on information available in the narrative incident report. Each coded variable was classified as relating to a section of the epidemiologic triangle: agent, host, or environment. Descriptive statistics were obtained for the coded variables and Chi-Square Automatic Interaction Detector (CHAID) analysis was performed in order to identify associations between predictor variables. A total of 1,230 incident reports were obtained and, after data cleansing, a total 1,193 fatality reports remained. While only 12% of cases occurred on farms, the calculated incidence rate in the farming population (.62 per 100,000 population/year) is higher than the overall incident rate in the United States (.13 per 100,000 population/year). Descriptive statistics showed low helmet use (11.85% of fatal cases) and high use of alcohol and drugs (84.2% of fatal cases). The CHAID results showed significant associations between all types of variables: agent, host, and environment. The present study provides nationwide statistics on ATV fatalities, approaching risk factor analysis with regard to the agent-host-environment epidemiological model. The three aspects of the epidemiologic triangle each contribute, and build upon each other, to create the combination of risk factors that lead to a fatal event. By modeling and categorizing risk it is possible to develop targeted solutions to the root cause of the hazard. Through use of legislation and training, many host-related risk factors can be controlled, use of engineering controls can mitigate risk due to the agent and/or physical environment, and use of targeted marketing strategies and education may be able to limit risk due to the social environment.